Principles of the just distribution of benefits and burdens: The "basic social justice orientations" scale for measuring order-related social justice attitudes - Stefan Liebig; Sebastian Hülle; Meike May (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
The paper introduces a short scale for measuring attitudes to four fundamental principles of the just distribution of benefits and burdens in a society. The Basic Social Justice Orientations (BSJO) scale is an eight-item scale that measures agreement with the equality, equity, need, and entitlement principle. In contrast to comparable other scales that have been used in justice research in the past, the BSJO scale is consistent with the current state of empirical justice research andallows for the study of the constructs distinguished by studies in that area and, more specifically, in the context of population surveys and with respect to societal distribution conflicts. The paper reports the methodological aspects of the construction and use of the scale in population surveys, as well as results concerning reliability and construct validation. The study uses data from three general social surveys that have been conducted in Germany: LINOS-1, SOEP Innovation Sample 2012, and ALLBUS 2014. The analysis of these three data sets confirms the assumed four-factorial structure of the justice dimensions, and the validation of the construct confirms the hypothesized relationships between the dimensions of the BSJO scale and socio-structural characteristics, political attitudes, and other justice related attitudes.
Keywords: 330; social justice; justice attitudes; distributive justice; justice ideologies; attitude measurement; survey research; equity; equality; entitlement; need